PENGARUH PENGGUNAAN INFLUENCER, STRATEGI PEMASARAN MELALUI MEDIA SOSIAL, SERTA INOVASI PRODUK TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK KULINER DI PENDOPO ASRI TRAWAS MOJOKERTO - Ivana Hilary Darmawan; Irra Chrisyanti Dewi (ITB AAS Indonesia Surakarta, 2026)
The aim of this study to analyse how Pendopo Asri Trawas's use of social media marketing, product innovation, and influencer marketing influences customers' final purchasing decision. In order to get at quantitative data, this study used a survey methodology and sent out questionnaires to 199 people who had bought something before. The data were analyzed using PLS-SEM, which stands for Partial Least Squares Structural Equation Modeling. Based on the findings, influencer marketing (β = 0.348; t = 5.166; p = 0.000) and social media marketing (β = 0.492; t = 7.787; p = 0.000) both have a favorable and substantial impact on purchase choices. Purchasing choices are unaffected by product innovation (β = 0.101; t = 1.419; p = 0.156). The R² value of 0.804 indicates that product innovation, social media marketing, and influencer marketing explain 80.4% of the factors influencing consumer choice. According to these results, digital marketing tactics have a greater impact on consumers' purchase choices in the modern day than does product innovation. Therefore, culinary business practitioners are encouraged to optimize social media marketing and collaborate with influencers to enhance consumer purchasing decisions.